Investigating prevalence job stress and illness among hospital staff providing health tourism services (HSPHTS) in Iran - Farhad Hemmati; Fatemeh Dabbaghi; Ghahraman Mahmoudi (BMC, 2020)
Abstract Background Health tourism or treatment tourism is one of threatening fields that causes (added s) increase in prevalence of job stress and illnesses among hospital staff of providing health tourism services (HSPHT). The aim of this study is to determine the prevalence of job stress and illnesses among hospitals staff of providing health tourism services in touristic cities as Tehran and Shiraz in Iran. Methods This cross-sectional, descriptive-analytical study was carried out among the staff of 10 hospitals providing health tourism services in cities of Tehran and Shiraz, Iran, in 2019. In these hospitals, 1250 staff were chosen by cluster sampling method from each job task as doctor, nurse, office worker, and paramedical and cleaner worker. Also, 1100 staff working in other general hospitals (non-HSPHTS) were selected as the control sample. Then, the demographic information and prevalence of job stress were gathered by Osipow job stress questionnaire and the illnesses were accumulated by self-reporting questionnaire. Finally, data were analyzed in SPSS 20 software. Chi-square and Pearson's parametric tests were used in the study. Results Prevalence of illnesses among HSPHTS was more than that in general hospitals (P value < 0.05). The most prevalent illnesses were respiratory (11.08%), digestive (9.2%), and cutaneous (9.04%), respectively. Also, the prevalence of job stress among HSPHTS was more than that in general hospitals (P value < 0.05). There was a significant relationship between prevalence of illnesses and job stress among the staff of hospitals and the increase in the number of visited tourists in the hospitals providing health tourism services. Conclusion Results of the study showed that the prevalence of job stress (%33.76) and illnesses (%43.66) among the HSPHTS was respectively 2 and 2.6 times more than that among the staff of general hospitals. Thus, it is necessary to observe sanitary actions and considerations more seriously in these hospitals.